Synthetic ceramide analogues as skin permeation enhancers: structure-activity relationships - Vávrová, Katerina; Hrabálek, Alexandr; Dolezal, Pavel; Sámalová, Lucie; Palát, Karel; Zbytovská, Jarmila; Holas, Tomás; Klimentová, Jana (Bioorganic & medicinal chemistry, 2003)
The study presents new information about the structure-activity relationships of the skin permeation enhancers. A series of ceramide analogues including eight different polar head groups and six different chain lengths was synthesised. The compounds were evaluated as permeation enhancers in vitro using porcine skin. The physico-chemical parameters of the tested compounds obtained by computer modelling were used to evaluate, by multiple linear regression, the enhancement ratios (ERs) of the compounds. The regression analysis suggests that the hydrogen bonding ability of the compounds is inversely related to the ER values and that the molecular size and lipophilicity must be well balanced. In the studied enhancers having the same chain length, the enhancement activity is dependent only on their permeability coefficients. This finding confirms the Warner's hypothesis that the polar head of an enhancer is responsible for the permeation and anchoring of the molecule into the stratum corneum lipids and that it does not influence the mechanism of action. For the specific action of enhancers, that is disordering of the intercellular lipid packing, the length of the hydrophobic chain(s) and not the lipophilicity is important. Furthermore, the examination of the FTIR spectra indicated that the most active substances possess the most ordered chains. The described relationships could bring more rational approaches in designing new potent enhancers for transdermal formulations.
Keywords: molekulární struktura; prasata; Molecular Structure; Permeability; Swine; techniky in vitro; permeabilita; kvantitativní vztahy mezi strukturou a aktivitou; Quantitative Structure-Activity Relationship; Animals; Ceramides; vodíková vazba; Hydrogen Bonding; kůže; Skin; ceramidy; zvířata; In Vitro Techniques